Уральские сказы - Бажов Павел Петрович (Советская Россия, 1987)
Экземпляры: ф.9 (1987) / Инвентарный номер: 14785 / Цена: 1.80 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 16 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6